2015
DOI: 10.1002/jat.3098
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine‐disrupting potentials of equine estrogens equilin, equilenin, and their metabolites, in the medaka Oryzias latipes: in silico and DNA microarray studies

Abstract: Although several previous studies have demonstrated the presence of equine estrogens in the aquatic environment, limited data are currently available on the endocrine-disrupting potentials in fish and the risks they pose to aquatic organisms. To investigate the interactions of major equine estrogens equilin (Eq) and equilenin (Eqn), as well as their metabolites 17α-dihydroequilin, 17β-dihydroequilin, 17α-dihydroequilenin and 17β-dihydroequilenin, with the estrogen receptor α (ERα) of medaka (Oryzias latipes), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Table 2 summarizes the key amino acid residues in the hydrogen-bonding interactions of the medaka/carp ERα-BP complexes. Among these amino acids, glutamic acid commonly interacted with the three BPs in both medaka and carp ERα, as well as our previous study using the medaka ERα and equine estrogens (Uchida et al, 2015). Similar observation was also reported in the docking simulation analysis between the rainbow trout ERα and perfluoroalkyl acids (Benninghoff et al, 2011).…”
Section: Comparison Of Bp Interactions Between Medaka and Carp Erαsupporting
confidence: 73%
See 2 more Smart Citations
“…Table 2 summarizes the key amino acid residues in the hydrogen-bonding interactions of the medaka/carp ERα-BP complexes. Among these amino acids, glutamic acid commonly interacted with the three BPs in both medaka and carp ERα, as well as our previous study using the medaka ERα and equine estrogens (Uchida et al, 2015). Similar observation was also reported in the docking simulation analysis between the rainbow trout ERα and perfluoroalkyl acids (Benninghoff et al, 2011).…”
Section: Comparison Of Bp Interactions Between Medaka and Carp Erαsupporting
confidence: 73%
“…The interaction potential of BPC (U-dock: À 77.27 kcal/mol) for the medaka ERα LBD was the most potent (stable), followed by BPAF ( À 71.47 kcal/mol) and BPA ( À 48.03 kcal/mol) ( Table 2). By comparing these data with E2 (U-dock: À 59.50 kcal/mol) which was previously reported by Uchida et al (2015), BPC and BPAF showed potent binding potentials for the medaka ERα LBD. Our in vivo study also showed that BPC and BPAF were at least 10-100 times more potent than BPA for upregulating hepatic Vtg and Chg genes ( Fig.…”
Section: In Silico Homology Modeling Of Medaka Erα and Bp Docking Simmentioning
confidence: 69%
See 1 more Smart Citation
“…The male medaka (approximately 6 months after hatching) was exposed to 17β‐E 2 and six equine estrogens according to the previously reported method (Ishibashi et al, ; Yamauchi et al, ). The exposure concentrations of these compounds were selected on the basis of the previously reported studies (Yamaguchi et al, ; Tyler et al, ; Uchida et al, ). Briefly, fish ( n = 6 per group) were exposed to each of the following conditions: 17β‐E 2 (nominal concentration: 1, 10, 30, 100 and 300 ng l −1 ), Eq (1, 10, 30 and 100 ng l −1 ) and other equine estrogens (1, 10, 30, 100 and 300 ng l −1 ) in 1‐l glass beakers for 3 days at 25 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…With another study they also reported the significant induction of plasma Vtg synthesis in rainbow trout ( O. mykiss ) and in carp ( Cyprinus carpio ), both of the fish species had been exposed to Eqn and 17β‐Eqn for 21 days, suggesting in vivo estrogenic potencies of these compounds in roach as well. Furthermore, our recent study demonstrated the interaction potential of six equine estrogens with the ligand‐binding domain (LBD) of medaka ERα in silico , and a DNA microarray analysis revealed up‐regulation of estrogen‐responsive genes such as Vtgs and Chgs in the liver of male medaka that were exposed to 100 ng l −1 each of Eq and Eqn (Uchida et al, ). However, no comprehensive data are yet available regarding the estrogenic potentials and risks of these equine estrogens to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%